PENINGKATAN KUALITAS PEMBELAJARAN IPA MELALUI STRATEGI BELAJAR CONCEPT MAPPING DENGAN MEDIA POWERPOINT - Vivi Astuti Nurlaily; Sri Hartati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2016)
The purpose of research was to improve the quality of science instructional through concept mapping learning strategy with media powerpoint. This design of research used a classroom action research that takes place in three cycles include the planning, implementation, observation, and reflection. Data collection techniques using test and non-test. Data were analyzed using descriptive analysis techniques of quantitative and qualitative. The results that the skills of teacher, student activity shown increase significant by was better category, and student respon increase by very positive. Impact to the result were was the best for learning product.